HUBUNGAN PENGGUNAAN SMARTPHONE DENGAN POLA TIDUR PADA ANAK KELAS IV DAN V DI SDN KRAMATJEGU 1 TAMAN SIDOARJO - Faridah, Faridah (Journal of Public Health Science Research (JPHSR), 2022)
Smartphone usage in children if not controlled can have an impact on health, one of which is lack of sleep needs anathoer factor that can affect sleep is fatigue after physical activity such as traditional play. This study will identify of smartphone usage, traditional play activities, sleep patterns in children, analyze the relationship of using smartphone with sleep patterns and analyze the relationship traditional play activities and sleep patterns.The study used design observasional design with cross-sectional approach. The independent variable was the use of smartphone , traditional play activity and the dependent variable was sleep patterns. The sample were 54 children on smartphone use and 54 children on traditional play activities, used probability sampling technique with the Stratified random sampling approach. The instrument on this study used questionnaire SAS , traditional play activities and PSQI, analyzed were by Spearman rho test. The results showed the level of smartphone usage is at most moderate (50.0%) and traditional play activities is at most highest (40.7%) with sleep patterns on smartphone use moderate (51.9%) and with sleep patterns on traditional play activities good (44.4%). Spearman rho test showed there is no relationship between using smartphone with sleep patterns r= 0.572 (r≤a = 0.05) and there is no relationship between traditional play activities with sleep patternsr= 0.481 (r≤a = 0.05). Implications of the results showed the use of no smartphone usage don’t have relationship with sleep patterns in children and there is traditional play activities don’t have relationship with sleep patterns in children. This research is useful for parents in monitoring play activities carried out by children